Functional screening of metagenomics libraries to find cellulolytic enzymes - Sousa, Joana Raquel Fernandes (2020)
The vast diversity of unexplored microbial communities inhabiting the planet drives the continuous screening for promising biocatalysts. Until recently, the strategies to find new microorganisms and their enzymes were mainly focused on laboratory studies of pure microbial cultures. However, a great amount of environmental microorganisms cannot be cultivated in laboratorial conditions. Metagenomics has emerged as an innovative and strategic approach to explore these uncultivable microorganisms through the analysis of DNA extracted from environmental samples. Two different approaches have been proposed for metagenome research, namely function- and sequence-based technologies. Sequence-based studies identify candidate genes but do not provide direct conclusions about the functionality of the encoded enzymes. On the other hand, the function-based approach allows the identification of new enzymes and also leads to preliminary information about their activities and physicochemical parameters. Indeed, function-based screenings have been successfully used in different environments to identify genes encoding lignocellulose-degrading enzymes, such as cellulases, xilanases or laccases. These enzymes are considered important catalysts in the biological decomposition of lignocellulosic residues. In this study, a fosmid library previously prepared with genomic DNA extracted from composting residues was evaluated through a functional screening. To assess the cellulolytic activities of the Escherichia coli clones, fast and simple screening tests were used and the results obtained were carefully compared. The screening tests were performed in agar plates with the addition of suitable chromogenic or non-chromogenic substrates to the culture media. For the non-chromogenic substrate, appropriate dyes were used for staining and detection of potential enzymatic activity. In this comparative study, it was concluded that some substrates and methodologies are more suitable and practical for the identification of cellulolytic positive clones.